ANALISIS JALUR PENGARUH KEPERCAYAAN KONSUMEN DAN DESAIN WEBSITE TERHADAP MINAT BELI ULANG, DENGAN ECOMMERCE SEBAGAI VARIABEL INTERVENING: STUDI KASUS PADA PRODUK E’CHICK SECARA ONLINE - Elia Rapha Tister Nursalim; Trianggoro Wiradinata (Universitas Ciputra Surabaya, 2016)
E'Chick is a frozen food manufacturer which processes chicken into chicken meatballs. These meatballs have high nutrient and various flavours. They are also halal, preservative-free, and healthy. The purpose of this research is to reveal the influence of consumer trust and website design on e-commerce, as well as the influence of product quality and e-commerce on repeat order. This research is a quantitative research. Random sampling is used as sampling technique to select 127 respondents. The variables in this study are product quality, consumer trust, website design, e-commerce, and repeat order. Questionnaire is used as data collection method in this study. The Schumacker and Lomax method is used in the questionnaire, while SPSS and AMOS software are used to process the questionnaire. Research results suggest that consumer trust and website design significantly influence e-commerce. Additionally, e-commerce positively and significantly influences the consumer's repeat order. According to the result obtained must have a concern on a website design to create repeat online order.